On node reproduction attack in wireless sensor networks - Harini, P. (International Journal of Engineering and Technology, 2017)
WSNs (Wireless Sensor Networks) comprise a large number of small, inexpensive, low power and memory constrained sensing devices (called sensor nodes) that are densely deployed to measure a given physical phenomenon. Since WSNs are commonly deployed in a hostile and unattended environment, it is easy for an adversary to physically capture one or more legitimate sensor nodes, re-program and re- deploy them in the network. As a result, the adversary becomes able to deploy several identical copies of physically captured nodes in the network in order to perform illegitimate activities. This type of attack is referred to as Node Replication Attack or Clone Node Attack. By launching node replication attack, an adversary can easily get control on the network which consequently is the biggest threat to confidentiality, integrity and availability of data and services. Thus, detection and prevention of node replication attack in WSNs has become an active area of research and to date more than two dozen schemes have been proposed, which address this issue. In this paper, we present a comprehensive review, classification and comparative analysis of twenty five of these schemes which help to detect and/or prevent node replication attack in WSNs.